Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's solve the given equation step by step.
We start with the equation:
[tex]\[ 2^{x+1} + 2^x - 2^{x-1} = 28 \][/tex]
We will use properties of exponents to simplify this equation.
First, let's express each term using properties of exponents:
- [tex]\( 2^{x+1} \)[/tex] can be rewritten as [tex]\( 2 \cdot 2^x \)[/tex] because [tex]\( 2^{x+1} = 2^x \cdot 2^1 = 2 \cdot 2^x \)[/tex].
- [tex]\( 2^{x-1} \)[/tex] can be rewritten as [tex]\( \frac{2^x}{2} \)[/tex] because [tex]\( 2^{x-1} = 2^x \cdot 2^{-1} = \frac{2^x}{2} \)[/tex].
Substituting these into the original equation:
[tex]\[ 2 \cdot 2^x + 2^x - \frac{2^x}{2} = 28 \][/tex]
Now, let's combine like terms:
[tex]\[ 2 \cdot 2^x + 2^x = 3 \cdot 2^x \][/tex]
[tex]\[ 3 \cdot 2^x - \frac{2^x}{2} = 28 \][/tex]
The term [tex]\( \frac{2^x}{2} \)[/tex] is equal to [tex]\( 0.5 \cdot 2^x \)[/tex], so we can rewrite the equation as:
[tex]\[ 3 \cdot 2^x - 0.5 \cdot 2^x = 28 \][/tex]
Combine the coefficients of [tex]\( 2^x \)[/tex]:
[tex]\[ (3 - 0.5) \cdot 2^x = 28 \][/tex]
[tex]\[ 2.5 \cdot 2^x = 28 \][/tex]
To isolate [tex]\( 2^x \)[/tex], divide both sides of the equation by 2.5:
[tex]\[ 2^x = \frac{28}{2.5} \][/tex]
[tex]\[ 2^x = 11.2 \][/tex]
Now we need to solve for [tex]\( x \)[/tex]. To do this, we need to take the logarithm of both sides. We typically use logarithm base 2 for problems involving powers of 2, but logarithm base 10 or the natural logarithm (base [tex]\( e \)[/tex]) can also work with appropriate conversions. Here, we are using the properties of natural logarithms (base [tex]\( e \)[/tex]):
[tex]\[ x = \log_2(11.2) \][/tex]
This expression can be converted to use the natural logarithm:
[tex]\[ x = \frac{\ln(11.2)}{\ln(2)} \][/tex]
Given the preceding steps and conversion:
[tex]\[ x = \frac{\ln(56/5)}{\ln(2)} \][/tex]
The solution can be expressed as:
[tex]\[ x = \frac{-\ln(5) + \ln(56)}{\ln(2)} \][/tex]
Thus, the value of [tex]\( x \)[/tex] is:
[tex]\[ x = \frac{\ln(56) - \ln(5)}{\ln(2)} \][/tex]
This is the precise solution to the given equation [tex]\( 2^{x+1} + 2^x - 2^{x-1} = 28 \)[/tex].
We start with the equation:
[tex]\[ 2^{x+1} + 2^x - 2^{x-1} = 28 \][/tex]
We will use properties of exponents to simplify this equation.
First, let's express each term using properties of exponents:
- [tex]\( 2^{x+1} \)[/tex] can be rewritten as [tex]\( 2 \cdot 2^x \)[/tex] because [tex]\( 2^{x+1} = 2^x \cdot 2^1 = 2 \cdot 2^x \)[/tex].
- [tex]\( 2^{x-1} \)[/tex] can be rewritten as [tex]\( \frac{2^x}{2} \)[/tex] because [tex]\( 2^{x-1} = 2^x \cdot 2^{-1} = \frac{2^x}{2} \)[/tex].
Substituting these into the original equation:
[tex]\[ 2 \cdot 2^x + 2^x - \frac{2^x}{2} = 28 \][/tex]
Now, let's combine like terms:
[tex]\[ 2 \cdot 2^x + 2^x = 3 \cdot 2^x \][/tex]
[tex]\[ 3 \cdot 2^x - \frac{2^x}{2} = 28 \][/tex]
The term [tex]\( \frac{2^x}{2} \)[/tex] is equal to [tex]\( 0.5 \cdot 2^x \)[/tex], so we can rewrite the equation as:
[tex]\[ 3 \cdot 2^x - 0.5 \cdot 2^x = 28 \][/tex]
Combine the coefficients of [tex]\( 2^x \)[/tex]:
[tex]\[ (3 - 0.5) \cdot 2^x = 28 \][/tex]
[tex]\[ 2.5 \cdot 2^x = 28 \][/tex]
To isolate [tex]\( 2^x \)[/tex], divide both sides of the equation by 2.5:
[tex]\[ 2^x = \frac{28}{2.5} \][/tex]
[tex]\[ 2^x = 11.2 \][/tex]
Now we need to solve for [tex]\( x \)[/tex]. To do this, we need to take the logarithm of both sides. We typically use logarithm base 2 for problems involving powers of 2, but logarithm base 10 or the natural logarithm (base [tex]\( e \)[/tex]) can also work with appropriate conversions. Here, we are using the properties of natural logarithms (base [tex]\( e \)[/tex]):
[tex]\[ x = \log_2(11.2) \][/tex]
This expression can be converted to use the natural logarithm:
[tex]\[ x = \frac{\ln(11.2)}{\ln(2)} \][/tex]
Given the preceding steps and conversion:
[tex]\[ x = \frac{\ln(56/5)}{\ln(2)} \][/tex]
The solution can be expressed as:
[tex]\[ x = \frac{-\ln(5) + \ln(56)}{\ln(2)} \][/tex]
Thus, the value of [tex]\( x \)[/tex] is:
[tex]\[ x = \frac{\ln(56) - \ln(5)}{\ln(2)} \][/tex]
This is the precise solution to the given equation [tex]\( 2^{x+1} + 2^x - 2^{x-1} = 28 \)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.